A new look at magnetic white dwarfs. Issue Volume 15:Issue S357(2019) (October 2019) - Hardy, François; Dufour, Patrick; Jordan, Stefan
Abstract: We present a homogeneous analysis of a large sample of magnetic white dwarf stars (with SDSS, PanSTARRS and Gaia data) using state-of-the-art magnetic atmosphere models and fitting techniques. We discuss the properties of the sample as well as the implication on our understanding of the nature and evolution of such objects.